PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN TOYOTA KIJANG INNOVA DI KOTA SEMARANG (Studi Kasus Pada Pengguna Toyota Kijang Innova di Kota Semarang) - Larasrini, Mreta Azizah; Hidayat, Wahyu; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2015)
This study aimed to analyze the effect of pricing, product quality, and brand image on purchase decisions Toyota Innova in Semarang. This type of research is explanatory research, the number of respondents 100 people with purposive sampling technique. Data collection techniques in this study using questionnaires, interviews, and observations. The data obtained were analyzed qualitatively and quantitatively by using tools such as cross-table analysis, validity, reliability and linear regression.Based on the analysis of the study variables price, product quality and brand image have a positive influence on purchase decisions. Brand image variables have the most impact in the amount of 36.3%. Variable quality of the product has the effect of 21.9% and the price variable has the effect of 18.2%. Taken together (simultaneously) the variable price, product quality and brand image has a 42.3% influence on purchasing decisions.The conclusion of this study there are significant hargaa positifantara, product quality, and brand image on purchase decisions Toyota Innova. Suggestions for the company by maintaining and improving the quality oroduk-kekuranganya deficiency and add facilities attractive exterior and interior so as to provide different values of the other products. Besides maintaining a good image in a way keep in constant communication with consumers and customers.